Effects of different soil management practices on soil mechanic resistance and seed depth placement in a maize crop in Alentejo, Portugal Mediterranean region - Conceição, Luis (2014)
In Alentejo region, Portugal, maize crop field studies were conducted to compare the effect of different tillage systems and no tillage in seed depth placement. Seed depth placement was measured by maize mesocotyl length after crop emergence under conventional tillage (CT), minimum tillage (MT) and no-tillage conditions (NT). In no-tillage condition two work speeds, 4km-1 and 6 km-1, were tested.